2019
DOI: 10.2478/mme-2019-0031
|View full text |Cite
|
Sign up to set email alerts
|

A thermoelastic microelongated layer immersed in an infinite fluid and subjected to laser pulse heating

Abstract: The present investigation deals with the twodimensional deformation because of laser pulse heating in a thermoelastic microelongated layer with a thickness of 2d, which is immersed in an infinite nonviscous fluid. Normal mode analysis technique is applied to obtain the analytic expressions for displacement component, force stress, temperature distribution, and microelongation. The effect of elongation and laser pulse rise time on the derived components have been depicted graphically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The system of prevailing equations of a microelongated thermoelastic solid with rotation, in the DPL model, as [4,7] (Fig. 1):…”
Section: Formulation Of the Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…The system of prevailing equations of a microelongated thermoelastic solid with rotation, in the DPL model, as [4,7] (Fig. 1):…”
Section: Formulation Of the Problemmentioning
confidence: 99%
“…The parameters 𝑀 , (𝑛 = 1, 2, 3, 4) and 𝑅 , (𝑛 = 1, 2, 3, 4) can be determined by using the boundary conditions at the surface are [3][4][5][6][7]:…”
Section: The Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sharma and Chauhan [8] also studied the impact of thermal as well as mechanical sources in a thermoelastic half-space in a generalized way. Ailawalia and Singla [9] derived the solution and reported a significant effect of laser pulse heating on all quantities in an immersed thermoelastic micro-elongated layer. Furthermore, Ailawaliaet al [10] also reported deformation of plain strain in a thermoelastic micro-elongated solid as an effect of laser pulse heating.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Ailawalia et al (2016) implemented the previous study in a new way, converting the elastic layer from a bounded layer to an unbounded layer. A two-dimensional deformation caused by laser pulse heating in a micro-elongated thermo-elastic layer with a thickness of 2 d engrossed in an infinite inviscid liquid was investigated by Ailawalia and Singla (2019). utilized normal mode analysis mechanism to create a model for a thermoelastic microelongated solid that takes into account the micro-elongation effect and laser pulse heating.…”
mentioning
confidence: 99%